Polarized Beam Dynamics and Instrumentation in Particle Accelerators USPAS Summer 2021 Spin Class Lectures - Méot, François; Huang, Haixin; Ptitsyn, Vadim; Lin, Fanglei (Particle Acceleration and Detection, 2023)
This Open Access book is drawn from lectures dispensed at the U.S. Particle Accelerator School (USPAS) Summer 2021 Spin Class, by experts in the field. It is an introduction to the dynamics of spin in charged particle accelerators, and to the accelerator components and spin manipulation techniques, including helical snakes and spin rotators, which enable and allow preserving beam polarization. It is aimed at graduate students or upper division undergraduate students with an interest in this multi-disciplinary field, which includes the future electron-ion collider at the Brookhaven National Laboratory, high energy lepton and proton collider projects, and other electric dipole moment search storage rings. It is also aimed at physicists or engineers working in accelerator-related fields who wish to familiarize themselves with spin dynamics and polarized beam concepts, tools, components, and purposes. This is an open access book.